2004
DOI: 10.1016/j.pbiomolbio.2003.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics as an emerging strategy for the investigation of central mechanisms in experimental hypertension

Abstract: Centrally mediated increases in sympathetic nerve activity and attenuated arterial baroreflexes contribute to the pathogenesis of hypertension. Despite the characterization of cellular and physiological mechanisms that regulate blood pressure and alterations that contribute to hypertension, the genetic and molecular basis of this pathophysiology remains poorly understood. Strategies to identify genes that contribute to central pathophysiologic mechanisms in hypertension include integrative biochemistry and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…However, aside from inducing MIF expression, icv-injected ANG II also induces expression of many other factors and genes (40), making it difficult to ascribe any physiological changes specifically to increased MIF expression. Therefore, to produce a selective increase in neuronal MIF within the PVN, it was overexpressed via Ad5-Syn-MIF.…”
Section: Discussionmentioning
confidence: 99%
“…However, aside from inducing MIF expression, icv-injected ANG II also induces expression of many other factors and genes (40), making it difficult to ascribe any physiological changes specifically to increased MIF expression. Therefore, to produce a selective increase in neuronal MIF within the PVN, it was overexpressed via Ad5-Syn-MIF.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic nervous (48, 91,133,198,240) and the reninangiotensin (48, 62,64,81,82,122,132,143,171,205,221) systems have been shown to be important in the pathogenesis of essential hypertension, including that associated with obesity (43). However, there are several counter-regulatory pathways (39, 76,135,142,169,174,184,205,219) (e.g., dopamine pathway), aberrations of which are involved in the pathogenesis of essential hypertension (3, 4, 8-18, 20, 21, 23-26, 29-33, 35, 37, 42, 44-46, 52-60, 67-70, 73-75, 77, 79, 80, 84, 86, 93-95, 97-103, 106-111, 114, 116, 118, 119, 124, 126-128, 130, 131, 136, 140, 141, 144-146, 148-156, 159-161, 163-166, 176-179, 182, 183, 186, 189, 192, 193, 195, 197, 203, 207, 209-216, 218, 224, 226-239), including that associated with obesity (16,37,201). Dopamine can regulate blood pressure by renal and nonrenal mechanisms (e.g., intestines and central nervous system) (93,130,131,207) that also involve the renin-angiotensin system (12,29,46,209,211,212,226,235,236).…”
mentioning
confidence: 99%
“…2,5 These studies have demonstrated that the expression of gammaadducin (␥-adducin), a cytosolic protein, is reduced in the hypothalamic-brainstem areas of the SHR. 6 ␥-Adducin belongs to a family of cytosolic proteins whose dimerization with an ␣ isoform plays a critical role in the control of cytoskeletal-mediated cellular processes.…”
mentioning
confidence: 99%